ANALISIS SISTEM PENGENDALIAN INTERN TERMIN PROYEK PADA MUTIARA MAS - Sultan Iskandar (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2015)
This study aims to determine the terms of the internal control system projects undertaken by the company PT. Mutiara Mas. While the analytical method used is comparative descriptive method that is an analysis that compares the internal control system of project terms tehadap elements of adequate internal controls. The results pembahsan in research that the admission procedure terms projects undertaken by the company PT. Mutiara Mas showing that the company in implementing the project acceptance procedures have not made the separation of functions between the financial section with receivables collection terms part of the project. Results of an analysis of the admission procedure terms projects the company has not perform authorization in the recording. So it can be said that the company in terms of revenue recognition procedures implementing the project yet reflect elements of internal control.